The Role of Lifestyle in Changes in the Menstrual Cycle in Anemic Adolescent Girls - Sri Yani (Journal of Contemporary Gender and Child Studies, 2023)
In the life cycle, adolescence is a period where teenagers will experience significant changes, both physically, psychologically and biologically, which can have an impact on aspects of their lives. This period is a transition period from childhood to adulthood, then teenagers begin to experience puberty. Puberty marks the onset of maturity in the reproductive system. This research aims to determine the relationship between knowledge between lifestyle patterns and changes in the menstrual cycle in students accompanied by iron deficiency anemia in young women in Indonesia. This research study is a literature review by drawing on all research in Indonesia regarding the relationship between knowledge of dietary status and changes in the menstrual cycle in adolescent girls. The benefit is to provide new knowledge about conditions that often occur in young women which can be caused by various factors such as nutritional status, healthy lifestyle, diet and changes in the menstrual cycle which decreases the body's resistance and causes the body to be susceptible to health problems. The results of this study show that there is a relationship between diet and lifestyle and the incidence of anemia that occurs in menstrual patterns with the same incidence. Thus, it is concluded that eating patterns and menstrual patterns are related to the incidence of anemia in adolescent girls and paying attention to the incidence of anemia in adolescent girls so as not to interfere with their achievements and hinder their educational goals.